REMOTE SEXUAL ASSAULT DI THAILAND: ANALISIS BERDASARKAN RESPON UNICEF - Nurbani Adine Gustianti; Rianne Octa Syahrani Anne; Gregory Henry Erari (Review of International Relations, 2022)
The phenomenon of sexual violence against children is increasingly common and has become global in almost all countries. Cases of sexual violence against children continue to increase from time to time. The increase is not only in terms of quantity or number of cases, but also in terms of quality. Thailand is one of the countries with the largest number of cases of child sex tourism in the world. Prostitution in Thailand plays a role in the country's economy. Ironically, most of Thailand's national income comes from the sex tourism sector. The issue of Human Security in Thailand has caused a decline in the image of the Thai state due to the many perspectives and poor responses on the issue of sexual violence. The reason is because of the history passed down from generation to generation since the Ayuthya era (1350-1767), economic problems, community culture, poverty levels, so that cases of sexual violence against children and women in Thailand are still ongoing today. The researcher uses a descriptive-analytical approach which collects various literature studies, composes, interprets the data, which is then analyzed to obtain valid data. By using the concept of Human Security and International Organizations to analyze the response of the United Nations Children's Fund (UNICEF), which is under the auspices of the United Nations, which emphasizes various issues related to children's rights, it is necessary to assist the Thai government in dealing with cases of child violence that occurred in Thailand. Then the results of the study show that based on the response from UNICEF and through several Remote Sexual Assault control programs, it has not been able to fully minimize sexual violence against children in Thailand.